Thermal Influence on the Stiffness of Hybrid Metal-Composite Countersunk Bolted Joints - Calin-Dumitru COMAN (National Institute for Aerospace Research “Elie Carafoli” - INCAS, 2021)
This paper presents the effects of temperature on the axial stiffness of a hybrid metal-composite countersunk bolted joint designed for the bearing failure mode. A detailed 3D finite element model incorporating geometric, material and friction-based full contact nonlinearities is developed to numerically investigate the temperature effects on joint stiffness. In order to validate the temperature effects, experiments were conducted using an Instron testing machine coupled to a temperature controlled chamber. The results showed that the temperature effects on axial joint stiffness were quite accurately predicted by the 3D finite element model, denoting a reduction in the stiffness of the axial joint with an increase in temperature for hybrid metal-composite countersunk bolted joints.